PENERAPAN NILAI-NILAI PANCASILA UNTUK MEMBENTUK KARAKTER MANDIRI SISWA KELAS IV DI SEKOLAH DASAR - Arif Prayudha; Asrial; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyse the application of Pancasila values in shaping the independent character of fourth grade students in elementary schools. The approach used was qualitative with a case study method at SD Negeri 121/1 Muara Singoan. Data were collected through observation, interview, and documentation. The results showed that the application of Pancasila values through daily activities at school, such as flag ceremonies, civic education lessons, and extracurricular activities, was effective in shaping students' independent character. Students become more disciplined, responsible, and have high self-confidence. Support from teachers and parents also play an important role in the success of this implementation. This research suggests that schools should continue to integrate Pancasila values in various activities to improve students' independent character building.